Efek Moderasi Kepemilikan Manajerial pada Hubungan Kinerja Keuangan dan Nilai Perusahaan: (Bukti dari Sektor Makanan dan Minuman di BEI) - Annisa Hasanah; Ninuk Dewi Kesumaningrum (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study examines the effect of financial performance measured through liquidity, profitability, and solvency on firm value, and tests the role of managerial ownership as a moderating variable in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was determined using purposive sampling, resulting in 28 companies with 98 observations after outlier elimination. Data were analyzed using Moderated Regression Analysis (MRA). The results show that liquidity and solvency have no significant effect on firm value, while profitability has a significant positive effect. Managerial ownership fails to moderate the effect of liquidity on firm value, but significantly strengthens the positive effect of profitability on firm value. Managerial ownership also significantly moderates the effect of solvency on firm value, although in the opposite direction from the hypothesis, strengthening rather than weakening the negative effect. These findings suggest that the role of managerial ownership as a governance mechanism is selective, depending on which financial performance indicator it moderates.